Drug‐induced enterocolitis syndrome: Similarities and differences compared with food protein‐induced enterocolitis syndrome. Issue 6 (29th March 2021) - Mori, Francesca; Liccioli, Giulia; Fuchs, Oliver; Barni, Simona; Giovannini, Mattia; Sarti, Lucrezia; Novembre, Elio; Caubet, Jean‐Christoph
Abstract: In 2014, drug‐induced enterocolitis syndrome (DIES) was described for the first time. It is still a poorly known disease with symptoms that typically resemble those of food protein–induced enterocolitis syndrome (FPIES). To date, six more cases of DIES have been described and new clinical diagnostic criteria have been proposed based on those in the international guidelines for FPIES. In this paper, the authors describe three more cases of DIES. In addition, similarities and differences with FPIES have been deeply analyzed. To date, several unanswered questions need to be addressed, but clinicians must be instructed how to identify DIES, in order to make an allergy workup and give definite therapeutic indications to patients, especially in children where DIES seems to be more frequent.